Pediatric Anesthesiology Review : Clinical Cases for Self-Assessment - Holzman, Robert S.; Mancuso, Thomas J.; Cravero, Joseph P.; DiNardo, James A. (Springer International Publishing : Imprint: Springer, 2017)
This text is designed for those who may become consultants in pediatric anesthesia. It is based on a curriculum developed since 1992 to illustrate the breadth and depth of the practice of pediatric anesthesia and the program is an integral part of the didactic series in the Department of Anesthesiology, Perioperative and Pain Medicine at Boston Children's Hospital. This second edition has the same purpose as the first - to accompany the reader's journey in attaining proficiency, expertise and finally, mastery in pediatric anesthesiology. The format of the book is designed to encourage the readers' free flow of ideas and the written examinations, seen at the beginning of the text as a baseline in pediatric medicine, are primarily knowledge-based, reflecting factual medical information necessary for the subspecialty practice of pediatric anesthesiology. With this basic guidance, the reader can bring him or herself "into the operating room" and manage the patient in an expert fashion.
Keywords: Medicine.; Anesthesiology.; elektronické knihy; electronic books